Factors contributing to female students’ enrolment in technical and vocational education in Nigeria - Yapilami, Anjili (2018)
Technical and Vocational Education and Training (TVET) is recognized as the bedrock for human, economic, and social capital development of any nation. It is a type of education by which an individual can acquire skills to live, learn and work as a productive citizen of a society. In Nigeria where women constitute more than half the total population, the number of women acquiring TVET is not proportional to their population. Research findings show this lop-sidedness right from point of admission into Polytechnics in Nigeria. This study is set to explore different factors contributing to female students’ enrolment in North-Eastern Nigeria, specifically to determine the levels and contributions of career awareness, cultural norms and values, vocational interest, and attitudes towards TVET programs among female students’ enrolment in TVET and Non-TVET programs. To determine the relationship between selected factors and predictors of female students’ enrolment in TVET and Non-TVET programs. The sample population of this study was 6,148 comprising of 3,984 Non-TVET and 2,164 TVET, ND II, female students in 9 Polytechnics of North-Eastern Nigeria. A sample size of 375 female students was selected using a multi-stage sampling technique to participate in the study. The final response rate was 92.5%, which amounted to a sample of 347 students. Quantitative research approach was employed. A structured questionnaire developed by the researcher and was used to collect data for the study. The Cronbach Alpha reliability test was carried out and a reliability coefficient of 0.85 obtained. Frequency, percentage, mean and standard deviation were used for the descriptive analysis, while Binary Multiple Logistic Regression was used to test the alternative hypothesis at 0.05 level of significance. The study found that both TVET and Non-TVET respondents have high level of career awareness, cultural norms and values, and vocational interest, which implied that these factors have a significant influence on female students’ enrolment in TVET programs. Therefore, the study found that career awareness, cultural norms and values, and vocational interest have a significant contributions on female students’ enrolment among TVET and Non-TVET programs in Nigeria Polytechnics. On the other hand, attitude towards TVET programs have shown no significant influence neither significant contributions to inadequate female students’ enrolment in TVET programs in Nigeria Polytechnics. In view of this, the study has established important factors to be highlighted on female students’ enrolment among TVET and Non-TVET programs. Government and other stakeholders in education sector should embark on awareness programmes through workshops and seminars to educate girls, women, parents and the general society on the benefits of TVET programs for women. Increase enlightenment programmes for females to overcome societal cultural norms and values is recommended. It is also recommended that affirmative action on employment of female lecturers in TVET programs employment should be emphasised so that female lecturers will serve as role model and encouragement to the female students. There should be incentives to encourage females to apply for admission into TVET programs especially in the "educationally disadvantaged” areas. The points required for admission into TVET programs should be made lower for females’ student than their male counterparts.